How do Women Fare in Education, Employment, and Health? A Gender Analysis of the 2006 Vietnam Household Living Standard Survey - World Bank (Washington, DC, 2012)
Along with remarkable achievements in reducing poverty during the past decade, Vietnam's social and economic development policies have placed much emphasis on promoting gender equality. From a perspective of gender equality, women in Vietnam are considered in a relatively favorable position compared with women in other developing countries or other developed Asian countries, with a high rate of women's labor force participation and a high degree of women's representation in political positions including the national assembly. With the new law on gender equality passed in November 2006, more policy efforts are called for in achieving gender equality in both public and private spheres of people's lives. In this context, it is all the more important to have up-to-date information on various indicators of gender equality in order to accurately assess the current situation of gender disparities in Vietnam. This task is essential for formulating policies that address specific problem areas of gender disparities, and for developing effective strategies for implementing and monitoring gender equality policies. The main objective of this report is to examine key indicators of women's social and economic lives with the most recent data, so that the authors have a better understanding of the nature and the extent of gender inequality in contemporary Vietnam. This will help to evaluate progress made thus far and identify areas for current and future challenges toward gender equality.